Synergy of Word-of-Mouth Marketing and Digital Branding in Educational Marketing Management in the Era of Disruption - Zainal Abidin; Akhmad Fauzi Hamzah; Ahmad Qusairi; Fadhel Mubarak (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2026)
This study examines the strategic management of educational marketing implemented at MAN Mempawah to enhance the institution’s competitiveness amidst digital disruption. Amidst increasing competition among educational institutions, reliance on single-channel marketing is no longer sufficient; therefore, a hybrid approach is needed. This study used a qualitative case study design. Data were collected through in-depth interviews with the madrasah principal and public relations staff, participant observation of marketing activities, and documentation of digital assets. The findings indicate that: (1) Marketing planning involves meticulous market segmentation and the development of unique value propositions through academic and non-academic excellence, such as specialized technology programs and religious curricula; (2) Implementation strategies rely on the synergy between traditional Word of Mouth (WOM) and modern Digital Branding. While WOM, driven by alumni achievements and community-based social programs (e.g., free medical treatment), builds deep trust, digital platforms such as Instagram, Facebook, and YouTube amplify this trust to a wider audience. The study concludes that the integration of “human-touch” social proof into “high-tech” digital narratives creates strong brand equity that significantly influences parental decision-making. The adaptive leadership of the madrasah principal in orchestrating these two poles is a key driver in maintaining the relevance and sustainability of madrasahs in the competitive educational landscape.